Indonesian Generation Z Work Expectation and Intention to Apply for Job: Role of Social Media - Inta Hartaningtyas Rani; Jara Hardiyanti Jalih; Lestari Adhi Widyowati (Yayasan Ahmar Cendekia Indonesia, 2022)
In the post-pandemic and disruption period, a company's talented human capital must be able to give competitiveness and agility. Considering the talent's expectations, businesses should provide an appealing employment environment. Using the SEM technique, the study analyses data on the intention to apply among 350 Indonesian nearly-graduated college students and implicitly validated the Gen Z work expectation scale empirically. The findings show that Generation Z's work expectations substantially impact their willingness to apply for jobs. When choosing a career, the top three considerations for respondents are health insurance, a coaching manager, and work security. Messages in job adverts should most likely appear on the company's social media account, emphasizing more psychological aspects that appeal to Generation Z's expectations, notably work benefits. Rather than having a moderating influence, social media direct connection strongly predicts job application intent.